Swing Pricing and Fragility in Open-End Mutual Funds. (8th March 2021) - Jin, Dunhong; Kacperczyk, Marcin; Kahraman, Bige; Suntheim, Felix
Abstract: How can fragility be averted in open-end mutual funds? In recent years, markets have observed an innovation that changed the way open-end funds are priced. Alternative pricing rules (known as swing pricing ) adjust funds' net asset values to pass on funds' trading costs to transacting shareholders. Using unique data on investor-level transactions in U.K. corporate bond funds, we show that swing pricing eliminates the first-mover advantage arising from the traditional pricing rule and significantly reduces outflows during market stress. Swing pricing also reduces concavity in the flow-performance relationship and dilution in fund performance.